World Wide Video Festival 1986 : catalogus. - Kijkhuis, Den Haag; World Wide Video Festival, Den Haag (Den Haag : Kijkhuis, 1986)
Adams, John ; Agosti, Silvano ; Almy, Max ; Alvarez Garcia, Julián ; Blumenthal, Lyn ; Bódy, Gábor ; Borofsky, Jonathan ; Glassman, Gary ; Brunner, Didier ; Burke, André Michael ; Byrne, James ; Cahen, Robert ; Callas, Peter ; de la Casinière, Joëlle ; Chase, Doris ; etc.
World Wide Video Festival 1986, Kijkhuis, Den Haag, 1986
Nederlands & Engels
boek